Lesson Study: Pembelajaran Berdiferensiasi Pasca Pandemi Covid-19 - Lestari, Andika Setyo Budi (Civiliza Publishing, Indonesia., 2023)
The Covid-19 pandemic hit almost all parts of the world, including Indonesia. It has been nearly two years since the pandemic hit, impacting various sectors, including education. During the pandemic, learning was carried out online and felt less effective. Various government efforts have been made for faster recovery, especially in education. One of the government's efforts is through the KDS program (Lecturer-Teacher Partnership in Schools) through Lesson Study activities. This study aims to see the implementation of a Lesson Study carried out together with junior high school teachers in partner schools. Through KDS (Lecturer-Teacher Partnership in School) activities by implementing Lesson study, compiling, and implementing differentiated learning. The research method used is the descriptive qualitative method. The subjects of this research were students of SMP Yadika Bangil. Lesson Study stages, namely planning (Plan), implementation (Do), and reflection (See), carried out with lecturers as facilitators and teachers in partner schools as model teachers and observers, have been carried out properly by Lesson Study guidelines and the learning objectives can be archieved planned. The results of research conducted through Lesson Studies led by teachers at school by implementing differentiated learning of student learning outcomes are mostly complete.